Dilema Pelimpahan Wewenang Walikota dalam Pelaksanaan Pelayanan Terpadu Kecamatan (PATEN) di Kota - Novie Indrawati Sagita (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
Regional autonomy provides broad and tangible authority to local governments to carry out public services. Acceleration of improving service quality requires creativity and innovation so that services can be carried out effectively and efficiently. The government wants public services to be closer to the community, so that the sub-district becomes the spearhead of services provided by the regional government. A set of regulations issued by the government that gives authority to the sub-district to carry out licensing and non-licensing services. One of the policies issued is the integrated sub-district administrative service (PATEN), this policy is reinforced by the issuance of Bandung City Regulation No. 185/2015 concerning the delegation of mayor's authority to the sub-district and village heads. PATENT policy requires the sub-district as a node of one-stop integrated services. In practice, there is a dilemma in delegating the authority of the mayor to the sub-district head regarding the implementation of PATENT in the city of Bandung. Some of the factors that inhibit the implementation of the PATENT include the limits of authority delegated to the sub-district head in the licensing service is unclear, there are different interpretations that the sub-district does not need to provide licensing services because Bandung has BPMPTSP besides geographically not too large so that service institutions it can be reached by the community, there is no incentive / disincentive for the region to implement or not implement integrated administrative services in the sub-district, the sub-district institutional capacity, especially the availability and competency of human resources that are not sufficient to carry out delegated service authority. Suggestions that can be conveyed regarding the implementation of the PATENT policy, must be considered that the delegation of authority should consider the typology of sub-districts based on the scale, type of service, impact and level of responsibility of the services provided.